Library of great Islamic literature : an encyclopaedic collection - Curtis, Herbert Pelham, translator (London : Koros Press Limited, 2012)
v. 1. Arabian Days' entertainments -- v. 2. Fairy tales from the Arabian nights -- v. 3. Gems of Arabic literature -- v. 4. Legends of ancient Egypt -- v. 5. Moorish literature -- v. 6. The story of Rustem -- v. 7. Ottoman literature -- v. 8. Persian tales -- v. 9. Popular stories of ancient Egypt -- v. 10. Stories from the Arabian nights -- v. 11. Arabic tales -- v. 12. Arabic tales -- v. 13. Oriental tales -- v. 14. Orient tales -- v. 15. Kalila and Dimna -- v. 16. Turkish literature -- v. 17. Turkish literature -- v. 18 The assemblies of Al Hariri -- v. 19. The assemblies of Al Hariri -- v. 20. Classical Persian literature -- v. 21. The garden of fragrance -- v. 22. The rose garden of Persia -- v. 23. The Bagh O Bahar -- v. 24. The Beharistan. (Abode of Spring) -- v. 25. The Shah Nameh of Firdausi